Migration and cardiovascular disease: a comparative study of prevalence and risk factor profiles in resettlers from the German National Cohort (NAKO) - Walther, Glenna; Brand, Tilman; Dragano, Nico; Meinke-Franze, Claudia; Führer, Amand-Gabriel; Greiser, Karin Halina; Hovardovska, Olga; Kiekert, Jamin; Krist, Lilian; Leitzmann, Michael; Lieb, Wolfgang; Mikolajczyk, Rafael; et al. (Annals of epidemiology, 2025)
Aims - Resettlers from the former Soviet Union are one of the largest migrant groups in Germany. Previous studies found lower cardiovascular disease (CVD) mortality among resettlers compared to Germans without migration background (autochthonous). Other studies have shown a higher prevalence of CVD risk factors among resettlers, suggesting a higher CVD mortality. The German National Cohort (NAKO) provides an opportunity to explore these discrepancies. - Methods - This study used baseline data from NAKO and compared age-adjusted percentages of self-reported CVD and associated risk factors between the two groups. Logistic regression models estimated adjusted odds ratios (OR) for associations between resettler status and outcomes. - Results - Among 204,751 participants aged 19-75, 3580 were resettlers and 169,538 autochthonous Germans. Male resettlers had lower odds of risky alcohol consumption (OR: 0.55; 95%CI: 0.49-0.63) but higher odds of ever smoking (OR: 1.26; 95%CI: 1.13-1.41) compared to autochthonous German men. Female resettlers showed higher prevalence of hypertension, diabetes mellitus, obesity, and elevated cholesterol/triglycerides, but lower prevalence of risky alcohol consumption and smoking. In men, the odds of peripheral artery disease (PAD) (OR: 0.46; 95%CI: 0.21-0.97) and any CVD (OR: 0.81; 95%CI: 0.66-0.98) were lower among resettlers. No other notable differences in clinical CVDs were observed in men. - Conclusion - Resettlers showed differences regarding CVD risk factor distribution compared to autochthonous Germans. These differences appear to balance out, leading to similar overall CVD prevalence, except for a lower prevalence of PAD and total CVD in male resettlers. Future longitudinal data will allow to explore long-term CVD trajectories. - Lay summary - We compared the prevalence of cardiovascular diseases (CVD) in a special group of migrants (resettlers from the former Soviet Union; German: (Spät-)Aussiedler) and autochthonous Germans, using data from the German National Cohort (NAKO) and investigated risk factors frequencies for these diseases in both groups. We found that male resettlers had less of risky alcohol consumption but smoked more than autochthonous German men. Female resettlers showed higher prevalence of hypertension, diabetes mellitus, obesity, and elevated cholesterol and triglyceride levels, but lower prevalence of risky alcohol consumption and smoking. The prevalence of most CVDs was similar in both groups, except of peripheral artery disease and all CVDs combined which we found less frequent in male resettlers.